PENGARUH E-SERVICE QUALITY TERHADAP REPURCHASE INTENTION MELALUI MEDIASI CUSTOMER SATISFACTION PADA PEMBELIAN MAKANAN SIAP SAJI (RICE BOWL) PADA TARGET PASAR USAHA DAPUR NUSANTARA - Djojokusumo, Jonathan Kevin; Efrata, Tommy Christian; Efrata, Tommy Christian; Kristanti, Lili; Kristanti, Lili (PERFORMA, 2023)
Dapur Nusantara is a business that runs in food field that sells products like rice bowl with Indonesian typical taste. The purpose of this research is to find out the effect of e-service quality on repurchase intention, e-service quality on customer satisfaction, customer satisfaction on repurchase intention, and e-service quality on repurchase intention through customer satisfaction as mediation variable. The population of this research is consumers of rice bowl products that have ever bought through social media with sampling method using Hair et al. formula, as many as 150 respondents. The analysis tool that is used is PLS-SEM with the assumption that each variable affects positively and significantly. The results of the research show that e-service quality affects significant positive on repurchase intention, e-service quality affects significant positive on customer satisfaction, customer satisfaction affects significant positive on repurchase intention, e-service quality affects significant positive on repurchase intention through customer satisfaction as mediation variable. The advantage of this research is the ease of taking respondents because of the large number of respondents who are consumers of rice bowl products. The benefit of this research is to find out what factors that affects consumers' repurchase intention on rice bowl products. Keywords: Dapur Nusantara, e-service quality, customer satisfaction, repurchase